Creating value from intellectual capital : an approach based on the specification of models - Cabrita, Maria do Rosário (2015)
Organizations are facing new competitive paradigms associated with the ability to create, use, combine, and manage intellectual assets. Intellectual capital is the primary driver in an innovation economy as it "processes" and leverages organizational value and improves creativeness. The purpose of this study is to examine the interrelationships among intellectual capital components within the Portuguese banking context and to identify the paths to a superior performance through the specification of models. These models are assessed using a PLS (Partial Least Squares) approach, because it is able to treat complex models and it requires less stringent assumptions. Empirical findings from this study support the proposition that intellectual capital is an important driver of organizational value. Moreover, intellectual capital is a phenomenon of interrelationships among human capital, structural capital and relational capital.